The myth of Ken Dedes in the mother cult of East Javanese society (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2021)
Ken Dedes is a figure who is remembered by the East Java community through myth and folklore. The myth of Ken Dedes is related to her figure as the primary woman who keeps the secret of radiant beauty, intelligence, and the mother who gave birth to the kings of Java. This study aims to find the reflection of people's memories about Ken Dedes and to find the cult of the mother from her figure. This research used a descriptive qualitative method with anthropological and psychological approaches. The results of the study show that Ken Dedes is remembered and reflected in the views of the people of East Java. From this reflection, the memory of Ken Dedes' serves as a projection or wishful thinking, an education tool, and a way of justification. In addition, in the context of the patriarchal society of East Java, Ken Dedes is a form of mother cult. In conclusion, the memory and reflection of Ken Dedes in East Javanese society have different variants based on the category of young and adult or old age. Meanwhile, the cult of the mother of a patriarchal society is legitimacy of throne.